2011
DOI: 10.1590/s0104-11692011000500022
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic and health characteristics of elderly individuals: support for health services

Abstract: This is a sectional epidemiological study including a household survey. It describes the socio-demographic and health conditions of elderly individuals residing in Guarapuava, PR, Brazil. The study's sample consisted of 359 elderly individuals enrolled in primary health care units in the city. Interviews were conducted from January to April 2010 using sections I and II of the Brazil Old Age Schedule questionnaire. The results revealed that most interviewees were women (64.3%), health self-perception was consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
10

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 12 publications
0
26
0
10
Order By: Relevance
“…Because it is a multidimensional instrument, it has been increasingly used in Brazil. 16 Their sessions allow us to describe the social determinants of the subject in question, whereas transposes into broader discussions as how these factors interfere with individual, family and group of elderly relationships. 17 The data were tabulated and analyzed using SPSS® 15.0 and it were obtained descriptive statistics (absolute frequency, percentage and confidence interval of 95%) for each of the variables.…”
Section: Methodsmentioning
confidence: 99%
“…Because it is a multidimensional instrument, it has been increasingly used in Brazil. 16 Their sessions allow us to describe the social determinants of the subject in question, whereas transposes into broader discussions as how these factors interfere with individual, family and group of elderly relationships. 17 The data were tabulated and analyzed using SPSS® 15.0 and it were obtained descriptive statistics (absolute frequency, percentage and confidence interval of 95%) for each of the variables.…”
Section: Methodsmentioning
confidence: 99%
“…In Brazil, in 2010, data collected from DATASUS pointed out that 23.3% of the population over the age of 18 reported previous medical diagnosis of hypertension (weighted percentage to adjust the socio demographic distribution of VIGITEL sample to the distribution of the adult population of Census 2000) (4) . A study involving the elderly population showed that 34.9% of all reported diseases referred to self-reported hypertension (5) .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, reports from well-designed, nationally representative and locally representative studies report rates ranging from 12.2% to 51.9% [17], [23]–[27]. Differences seem to reflect how arthritis is defined, how enquiry is phrased, and the time frame covered.…”
Section: Introductionmentioning
confidence: 99%